ANALYSIS OF STUDENTS' METACOGNITIVE AWARENESS AT MAS INSAN QUR'ANI THE DISTRICT OF ACEH BESAR - Fatemah Rosma; Mauizah Hasanah (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2023)
21st century education emphasizes students to have high-level thinking abilities. However, in reality it has not been realized well, which is indicated by the inability of students to make good planning arrangements in the learning process. This is closely related to the metacognitive abilities that students must have. This research aims to determine the percentage of metacognitive awareness of Biology learning at MAS Insan Qur'ani, Aceh Besar. The method used is a Mix Method research design with an explanatory sequential design. The research sample consisted of 30 students. The research instrument uses a sheet in the form of a Metacognitive Awareness Inventory (MAI) questionnaire to see students' metacognitive awareness. The analysis test was carried out using percentages and the Independent Sample t-test. The research results show that students' metacognitive awareness is in the good category with a percentage of 75.14%. The lowest indicator of metacognitive awareness is found in IMS with a percentage of 47%, while the highest indicator is in DK with a percentage of 49.03%. For the calculated t test, significant results were obtained with a value of tcount ttable (2,156 2,000). Metacognitive awareness is very good to use in the learning process. It is hoped that this research can be used in learning materials contained in biology learning. And it is also hoped that teachers can use various types of learning models to gain better metacognitive awareness of students so that they can think analytically in dealing with various problems found in Biology learning.